Prospects for the Political System of Ukraine in the Context of Global Geopolitical Transformations - A. V. Ishin (Проблемы постсоветского пространства, 2025)
The article analyzes political problems caused by the prospects of the political system of Ukraine in the context of global geopolitical transformations. The author examines the  geopolitical preconditions for the ukrainian crisis, characterizes the new geopolitical realities and  the “european factor”, and assesses the state and prospects of the ukrainian political system at the present stage. An important component of the new geopolitical realities was the proclamation of a course towards a peaceful settlement of the “ukrainian conflict” taking into account Russia’s interests, and the beginning of bilateral consultations in the Russia-USA format. Based on the interdisciplinary method of binary oppositions, the author notes that global geopolitical transformations have brought to the forefront with new urgency the dichotomy of “Russia and Europe,” which was conceptualized by N. Ya. Danilevsky back in the 19th century. Today, high-ranking officials of the European union are making unambiguous statements that a peaceful resolution of the crisis around Ukraine allegedly poses a threat to “european interests”. Against this background, the stagnation of the Ukrainian political system, in which nationalist ideologies reign supreme, is deepening. The author comes to the conclusion that this state of affairs is a  direct consequence of the preservation throughout all the years of the so-called “independence of  Ukraine” of the unitary administrative-territorial structure, the rigid imposition of the Western Ukrainian regional and mental identity on the residents of the other regions.